Ecosystem-based Adaptation by smallholder basic grain farms in Guatemala and Honduras - Chain-Guadarrama, Adina; Martínez-Rodríguez, M. R.; Cárdenas, José Mario; Vílchez-Mendoza, Sergio; Harvey, C. A. (Agronomía Mesoamericana, 2018)
In Central America maize and beans are usually cultivated by farmers who have small landholdings and live in vulnerable situations. Climate change is an important threat to these smallholder basic grain farmers, putting at risk their production systems and their livelihoods. The use of Ecosystem-based Adaptation (EbA) can help them to adapt to climate change, however there is limited information on the use of EbA. The objective of the present work was to characterize the EbA strategies that smallholder basic grain farmers of four landscapes in Guatemala and Honduras use to increase their resilience to climate change. Using interviews and field measurements in 160 farms, between July 2014 and June 2015, we 1) explored how common the use of different EbA practices is, 2) documented the biophysical characteristics of these practices, and 3) explored if the implementation and characteristics of EbA practices differed among landscapes. Our results indicate that even though they own small land areas (mean maize plot area of ~0.68 ha), have low education levels and low access to technical training and advice, many smallholder basic grain farmers are using EbA practices in their farms. The most common EbA practices were the use of dispersed trees, home gardens and live fences. An ANOVA anlysis indicated significant differences in the use of different EbA practices among farmers, which suggests that farmers adapt practices in response to the social and biophysical conditions where they live. Our study suggests that smallholder basic grain farmers have the experience and the knowledge to use EbA practices and recognize the benefits derived from the implementation of such practices. However, in order to increase use of EbA practices, more technical, financial and political support is needed.